Service-oriented computing : 13th International Conference, ICSOC 2015, Goa, India, November 16-19, 2015 : proceedings /: 13th International Conference, ICSOC 2015, Goa, India, November 16-19, 2015 : proceedings. (2015) - Unknown
No abstract available